Unveiling the role of gasdermin B in cancer and inflammatory disease: from molecular mechanisms to therapeutic strategies - Yang, Weixiao; Hu, Xu; Li, Xiang (PeerJ, 2025)
Gasdermin B (GSDMB) is a member of the gasdermin (GSDM) protein family, primarily known for mediating pyroptosis, an inflammatory form of programmed cell death. Recent studies have revealed the diverse molecular functions of GSDMB and its close association with various diseases, particularly cancers (e.g., breast cancer, gastric cancer, bladder cancer) and inflammatory diseases (e.g., asthma, inflammatory bowel disease). At the molecular level, GSDMB induces pyroptosis by forming pores in the cell membrane, leading to membrane rupture. This function is common across the GSDM protein family; however, GSDMB also exhibits unique non-pyroptotic functions, such as modulating cell proliferation, migration, and immune responses. In multiple cancers, including breast cancer, gastric cancer, and cervical cancer, high expression of GSDMB correlates with poor prognosis, promoting cancer cell proliferation, invasion, and metastasis through interactions with signaling pathways such as STAT3 and mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK). Additionally, GSDMB influences the immune microenvironment through its pyroptotic activity, playing a role in the initiation and regulation of inflammation. Upon activation, it can directly cleave target cells via its N-terminal domain, contributing significantly to chronic inflammatory diseases and NK cell-mediated antibacterial responses. In conclusion, as a multifunctional protein, GSDMB not only participates in pyroptosis but also regulates non-pyroptotic processes, playing an important role in cancer progression and inflammatory diseases. Further elucidating the detailed mechanisms of GSDMB may offer novel therapeutic avenues for these conditions.
Keywords: GSDMB; Cancer; Inflammatory disease; Therapeutic target; Pyroptosis